Using Non-native English Films to Promote Multiculturalism in ELT Classroom (Journal of NELTA, 2015)
This paper aims to present how the incorporation of non-native English films can enhance the multicultural awareness among the English language learners. As the non-native English films expose the students to linguistic and cultural diversity, they can be used as effective tools in designing materials for ELT classroom. To demonstrate how teachers can incorporate these films in their classroom, the paper discusses various approaches to design materials for language classroom, and contains three sample lesson plans for intermediate, upper-intermediate and advanced level students. The lesson plans exploit a number of non-native English films to generate a discussion of different cultures along with teaching English language. Finally, the paper ends with some suggestions for the teachers. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12081 Journal of NELTA, Vol 19 No. 1-2, December 2014: 65-76